Family firms types based on beliefs - Guadalupe Manzano-García; Jean-Pierre Neveu; Arkaitz Ba\~nuelos Campo; Juan Carlos Ayala Calvo (European Research on Management and Business Economics (ERMBE), 2023)
The purpose of this study was to find an effective way of identifying homogeneous family firm groups, based on the prevailing beliefs of the owning family on ownership, management and intergenerational transmission. We conducted a two-stage cluster analysis, using data from a representative sample of 240 Spanish family firms. The results showed three types of clearly differentiated family firms, each of them with a profile of different beliefs. Our work contributes to the previous literature by integrating the components of involvement and essence approaches and beliefs about these to distinguish homogeneous groups of family firms.
Keywords: D23; L02; M14; 650; Family firm; Beliefs; Cluster; Taxonomy